PENGEMBANGAN MODEL PERMAINAN BOLA BASKET UNTUK PENDIDIKAN JASMANI, OLAHRAGA, DAN KESEHATAN SISWA KELAS X, XI, XII SMAN 3 GORONTALO, SMKN 4 GORONTALO - PAUWENI, MIRDAYANI; DATAU, SURIYADI (Jurnal Health and Sport, 2013)
The Purpose of this research and development was to produce a developing product of basket ball of physical education, sport, and health to developing movement ability and it is not bias of gender and deal with growth and development of students high school and vocational high school. This is a research and development. The developing of the product of basket ball of physical education, sport, and health for high school and vocational high school students, was done through several stages: draft designing of the product, validation of experts, few scale experiment, the first of revision, large scale experiment, the second revision (the last revision). The subject of this research were the student of high school and vocational high school (SMU) Negeri 3 Gorontalo, SMK Negeri 4 Gorontalo. There were 61 students for subject of research. validation of experts was done by an experts and two physical education teachers. The few scale experiment was done to 11 students and the large scale experiment was done to 61 students. The data was collected by using questioner. The data consists of evaluation for product quality, suggestion for product improvement and student response to the model. The correlate Instrument validity shown that totality instrument was valid. Instrument reliability test shown by .720. The correlate shown that totality instrument was reliable. The Conclusion of this research was a nouti basket ball model for physical education, sports and health that can be use to developing movement ability of students, and can be use to raise students understanding of concept of cooperation, fair play, and honesty. Based on result of this research, the suggestion is the physical education elementary school teachers can use the product of basket ball model for physical, sport, and health education of students high school and vocational high school.